Monitoring LED Lights with Current Signatures - Verhoeff, Johnny; Nambi, Akshay; Zuniga, Marco; Humala, Bontor (ACM/IEEE INFOCOM, 2018)
Artificial lighting is a pervasive element in our daily lives. Researchers from different communities are investigating challenges and opportunities related to artificial lighting but from different angles: energy disaggregation, to monitor the status of light bulbs in buildings; and communication, to transmit information wirelessly. We argue that there is an unexplored synergy between these two communities. When a light bulb modulates its intensity for communication, it also affects the current it draws. This current signature is unique and could be used by energy disaggregation methods to identify the lights’ status. These signatures however will be exposed to interference (collisions of signatures) and distortions due to power line effects. To overcome these problems, we build upon coding schemes to assign interference-resilient signatures, and we develop custom hardware to ameliorate distortions introduced by power lines. We validate our framework in a proof-of-concept testbed, perform simulations to test scalability, and use energy traces from real homes to evaluate the impact of other electric loads.